Uji Organoleptik Produk Eco-Enzyme dari Sampah Organik - Octavia, Zana Fitriana; Zahroh, Fatimatuz; Hayati, Nur; Lestari, Puji; Sholichah, Farohatus (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Organic waste, such as food residues, can be processed into Eco-Enzyme, a product with various benefits. This study aims to produce Eco-Enzyme from organic waste and to conduct an organoleptic analysis of the resulting product. The research employed an experimental design for the production of Eco-Enzyme and a descriptive method for the organoleptic test. The Eco-Enzyme was made from vegetable and fruit waste mixed with palm sugar and water, then fermented for three months, with the container opened once every month. The results of the organoleptic test showed that most samples had a fermented aroma (60.29%), a light brown color (25%), and a constant volume (100%). The production process began with selecting organic waste, cutting it into small pieces, and then mixing it with palm sugar and water at a ratio of 1:3:10 (sugar:waste:water).